Association of Cytomegalovirus Infection With Anti-MDA5 Antibody-Positive Dermatomyositis: A Prospective Cohort Study - Huang, Linlin; Zhu, Wenbo; Ye, Yan; Wu, Xiaoping; Yan, Qingran; Wang, Zhiqing; Lin, Yanwei; Chen, Sheng (Frontiers in Medicine, 2021)
Objectives: To investigate whether cytomegalovirus (CMV) infection plays a role in the pathogenesis and prognosis of idiopathic inflammatory myopathy (IIM), particularly in anti-MDA5 antibody-positive (anti-MDA5+) dermatomyositis (DM). Methods: A prospective cohort of 204 newly diagnosed IIM patients and 50 healthy individuals were enrolled in the study. CMV-IgM and CMV-IgG antibody concentrations and lymphocyte counts were analyzed. Differences in categorical data were compared using Fisher's exact test and the chi-square test. One-year survival rates were analyzed in MDA5+ DM patients with and without CMV infection. Results: In IIM patients, the median CMV-IgM level was significantly higher than in healthy controls (6 U/mL vs. 0 U/mL, p < 0.05) as was the median CMV-IgG level (114 U/mL vs. 105 U/mL, p < 0.05). The percentage of recent CMV infections in the MDA5+ DM group was much higher than it was in the MDA5− IIM group (19.1% vs. 7.0%, p = 0.009). MDA5+ DM patients with CMV DNA-emia had poorer 1 year survival than the CMV-DNA− group (33.3% vs. 86.3%, p = 0.010). CMV-IgM-positive (CMV-IgM+) MDA5+ DM patients had lower CD4+ T cell counts (245.7 cells/μL vs. 420.5 cells/μL, p < 0.05) and CD19+ B cell counts (97.3 cells/μL vs. 240.6 cells/μL, p < 0.05). Conclusion: The number of CMV infections was significantly higher in IIM patients, particularly in MDA5+ DM patients. Lower CD4+ T cells and CD19+ B cells were observed in CMV-IgM+ MDA5+ DM patients. CMV infection may have an important role in the pathogenesis and prognosis of MDA5+ DM by disrupting immunity.